التمويل المصرفي الإسلامي للمؤسسات الصغيرة والمتوسطة - بن عمارة, نوال (جامعة الوادي - University of Eloued, 2012)
تهدف هذه الدراسة إلى إلقاء الضوء على التمويل المصرفي الإسلامي للمؤسسات الصغيرة والمتوسطة متناولاً مفهومها ومميزاتها وأهميتها ودورها في التنمية الاقتصادية والاجتماعية، واستعراض أهم المعوقات التي تواجهها في التمويل التقليدي، وصولا إلى اقتراح إطار لأساليب التمويل الإسلامية الملائمة لواقع وطبيعة المؤسسات الصغيرة والمتوسطة The purpose of this research is to shed light on the financing of Islamic banking for small and medium enterprises, addressing the concept and its advantages and its importance and its role in economic and social development, And review of the major constraints faced by the traditional funding, leading to propose a framework for Islamic finance methods appropriate to the reality and the nature of small and medium enterprises.
مقال
Keywords: التنمية الاقتصادية، التمويل المصرفي الإسلامي، للمؤسسات الصغيرة والمتوسطة; Economic development, Islamic banking finance, for small and medium